Ghrelin alleviates hypoxia/reoxygenation-induced H9C2 injury by activating autophagy and AMPK/ULK1 pathway: Ghrelin alleviated H/R induced H9C2 injury - Liu, Hui; Lv, Wei; Ouyang, Li; Xu, Li (Cellular and Molecular Biology, 2023)
The research aims to explore the protective effects of ghrelin and its underlying molecular mechanisms in an H9C2 hypoxia/reoxygenation model. H9C2 cells were transfected with ghrelin overexpression lentiviral vector. The hypoxia/reoxygenation H9C2 model was constructed. The expression of ghrelin was analyzed by qRT-PCR and Western Blotting. CCK8, flow cytometry and TUNEL assay were used to analyze the impact of ghrelin on the survival and apoptosis of H9C2 injured by hypoxia/reoxygenation. The levels of autophagy-related proteins in H9C2 cells were evaluated through Western blotting. ELISA was utilized to assess how ghrelin affects the inflammatory response triggered by hypoxia/reoxygenation. Western blotting was utilized to investigate the regulatory role of ghrelin on the AMPK/ULK1 pathway. Additionally, the AMPK inhibitor Compound C was introduced to delve further into the associated mechanism. Hypoxia/reoxygenation injury decreased the expression of ghrelin. Transfection of ghrelin overexpression lentiviral vector significantly increased the expression of ghrelin in H9C2 cells. Ghrelin overexpression can significantly promote cell survival, reduce apoptosis, activate AMPK, ULK1 and AMBRA1, promote autophagy, increase the expression of LC3BII/LC3BI and Beclin-1, reduce the expression of P62, and reduce inflammatory response. Ghrelin inhibited apoptosis of H9C2 caused by hypoxia/reoxygenation and reduced inflammatory response, which mechanism is related to activation of AMPK/ULK1 pathway and autophagy.